The effect of silane-coated slag mineral on the mechanical and dynamic mechanical properties of unsaturated polyester composite materials. Issue 15 (2nd August 2020) - Mousa, Ahmad; Gedan-Smolka, Michaela; Wagenknecht, Udo; Massadeh, Sami
Abstract: To determine the potential of a sustainable by-product from iron-making industry 'Slag' as reinforcing agent for thermoset polymer composite, particularly unsaturated polyester (UPE). The slag has been coated by reactive and nonreactive silanes. In the first stage, the slag was comminuted and sifted prior to silane coating. The silane-coating agent adsorbed on the surface of the slag was followed by thermogravimetric analysis (TGA) and attenuated total reflectance infrared spectroscopy (ATR-IR). The fabricated composites with various silane-coated slag were inspected with respect to tensile and flexural properties as a function of the coating agent. Scanning electron microscope was carried out on the composite with uncoated and silane-coated samples. The obtained findings indicated that the slag coated with amino and octyltrioxy-based silanes showed a positive impact on the mechanical performance. The improvement was related to the structure of coupling agent used.